Diffusion of Innovation Strategy to Preserve Traditional Culture - Kilau Riksaning Ayu; Itsna Hidayatul Khusna; Monika Herliana (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2025)
Indonesia's cultural preservation faces significant challenges in the era of globalization, especially in attracting the younger generation. This research explores the innovation diffusion strategy implemented by Larasati Art Studio in Purbalingga in efforts to preserve traditional culture. Using a qualitative case study methodology, data was collected through in-depth interviews and observations. The results show that Larasati Art Studio applies an innovation diffusion strategy through the gradual adoption of digital technology, starting with the use of Instagram, Google Business, and YouTube. This strategy is reinforced by active involvement in local and national art communities, which accelerates the innovation adoption process. The studio also combines digital innovation with active participation in various traditional art events, creating a holistic approach to cultural preservation. Although social media engagement levels still need improvement, this strategy has successfully increased the studio's visibility, member participation, and young people's interest in traditional arts. This research demonstrates how the Diffusion of Innovation Theory can be applied in the context of cultural preservation in Indonesia, supporting the achievement of SDGs, especially Goal 4 (Quality Education) and Goal 11 (Sustainable Cities and Communities).